Exposure to leachates of plastic food containers disturbs glucose and lipid metabolism: Insights from models mimicking real-exposure scenarios - Hu Liu; Peiqi Li; Tan Zhou; Ziqi Yu; Weigao Zhang; Yunfeng Zhu; Jiayi Xu; Xiaoxiao Wu; Jing Li; Chi Zhang; Lei Chen; Dan Weng (Ecotoxicology and Environmental Safety)
The increasing use of plastic food containers, particularly for pre-cooked meals and takeout services, has raised concerns regarding the potential health risks associated with plastic leachates. This study investigated the impact of leachates from heat-treated polypropylene (PP) plastic food containers on glucose and lipid metabolism using both in vitro and in vivo models. AML12 hepatocytes exposed to leachates from three different PP plastic containers exhibited significant disruptions in the homeostasis of lipid and glucose metabolism, evidenced by increased intracellular lipid content and altered gene expression related to lipogenesis, lipid uptake, lipolysis, and fatty acid β-oxidation. C57BL/6J mice were fed with the mouse diet that had been heated in two distinct types of PP plastic food containers for 8 weeks and these mice exhibited accelerated body weight gain, altered fasting blood glucose levels, and changes in serum lipid profiles. Histological analysis revealed increased adipocyte size, liver steatosis, and glycogen accumulation. Transcriptome sequencing of liver tissues highlighted significant alterations in the expression of genes involved in metabolic pathways, further corroborated by real-time qPCR validation. These findings underscore the potential metabolic health risks posed by the use of heated plastic food containers.